2016
DOI: 10.17116/oftalma2016132598-102
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography in glaucoma diagnosis

Abstract: Оптическая когерентная томография с функцией ангиографии в диагностике глаукомы Н.И. курыШеВА, е.В. МАСлоВА ФГБоу ДПо «Институт повышения квалификации» ФМБА, ул. Гамалеи, 15, Москва, 123098, российская Федерация Данные литературы свидетельствуют o вовлечении сосудистой дисфункции в патогенез глаукомной оптиконейропатии. Это делает обоснованным поиск новых методов визуализации для ранней диагностики и мониторинга глаукомы, направленных на изучение перфузии сетчатки, зрительного нерва и хориоидеи. Появившийся не… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…5,6 In addition, many studies have demonstrated high diagnostic values of OCTA in primary open-angle glaucoma (POAG) and NTG eyes, and VD in OCTA is also highly correlated with mean deviation (MD) and pattern standard deviation (PSD) values in the VF examination. 7,8 Because VF testing measures visual function, it is theoretically more relevant than OCTA. However, VF testing requires cooperation and concentration from the patients, meaning it has lower repeatability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In addition, many studies have demonstrated high diagnostic values of OCTA in primary open-angle glaucoma (POAG) and NTG eyes, and VD in OCTA is also highly correlated with mean deviation (MD) and pattern standard deviation (PSD) values in the VF examination. 7,8 Because VF testing measures visual function, it is theoretically more relevant than OCTA. However, VF testing requires cooperation and concentration from the patients, meaning it has lower repeatability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 In addition, many studies have demonstrated high diagnostic values of OCTA in primary open-angle glaucoma (POAG) and NTG eyes, and VD in OCTA is also highly correlated with mean deviation (MD) and pattern standard deviation (PSD) values in the VF examination. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%